Vitexicarpin inhibits overexpression of GNAO1 and plays a role in gastric cancer cell proliferation and apoptosis (Bangladesh Journal of Pharmacology, 2015)
The present study demonstrates the effect of vitexicarpin on down-regulation of GNAO1 in human gastric cancer cell lines. The results from Western blot analysis revealed that vitexicarpin treatment inhibited the GNAO1 expression in MKN-45 cells at a concentration of 30 µM. Examination of cell proliferation using CCK-8 cell proliferation kit showed 70% reduction in the vitexicarpin treated cells compared to untreated control cells. Cell cycle analysis using propidium Iodide staining followed by flow cytometry showed cell cycle arrest at G0/G1 with reduction of cell population in the S-phase. There was a significant aneuploidy in the controls compared to zero aneuploidy in the GNAO1 down-regulated cells. Transwell chamber and scratch wound healing assay respectively showed 65% and 42% reduction in migration of vitexicarpin treatedMKN-45 cells. Therefore, vitexicarpin treated inhibition of GNAO1can be a potential therapeutic strategy for the treatment of gastric cancer.